Not just one, but many ‘Rights to be Forgotten’ - Geert Van Calster; Alejandro Gonzalez Arreaza; Elsemiek Apers (Internet Policy Review, 2018)
Since being first developed through the case law of the European Court of Justice, the Right to be Forgotten (RTBF) has continued rapidly to evolve and has recently moved beyond its European borders. In recent times, RTBF has faced increasing debate and litigation, such as in Latin America. This paper focuses on the wide spectrum of interpretations RTBF has garnered across countries and data protection authorities. This paper compares relevant European or Latin American cases within each jurisdiction on the basis of four key variables. Case analysis showed that there is no unified approach to RTBF. This is especially true at the level of the defendants involved, that is, whether it involved the local subsidiary or the parent company, and whether the order of removal had local or 'global' effects, meaning the removal of content or access was addressed to a local or global domain. This last issue is paramount, since it will determine whether an order of removal would leave content available and accessible for anyone outside of the jurisdiction of the authority who orders it, or whether links to the content become inaccessible to everyone everywhere.